La Turquie : instrument de politisation, objet de politisation - Claire Visier (European Journal of Turkish Studies, 2015)
This paper analyses the politicization process in France of Turkey’s EU bid. In 2002 the President of the Convention on the future of Europe, V. Giscard d’Estaing, was one of the first leaders to take a strong political stand against Turkey’s EU bid. The first part of the paper demonstrates why and how this stand was an attempt to legitimize the European Union. The success of the first step of this politicization process is shown by the very strong impact in both European and French policies of V. Giscard d’Estaing’s claim. The second part of the paper covers French politicians’ use of the issue of Turkey’s EU bid. In 2004, several French politicians opposed Turkey’s EU bid in order to mobilize French citizens for the European elections. First considered as a tool because of its strong political power, the point of Turkey’s EU bid gradually vanished from the politicians’ strategies, to become an issue that they couldn’t manage as they wanted to. The issue rose not only as a resource but also as a handicap for French polity. The politicization process has also led to a particular framing of the issue which nowadays is still strong in French political polity and the public sphere.